PEMBUATAN ARANG DARI SAMPAH ORGANIK DENGAN CARA KARBONISASI MENGGUNAKAN REAKTOR PIROLISIS - Abdul Gani Haji (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2006)
Charcoal is possibly produced from municipal organic waste using pyrolysis reactor at a temperature of 350-510 oC for 5 hours. Parameters used for charcoal quality determination are: product quantity, water, ash, evaporated material, carbon, calorific value, iodine adsorption capacity, benzene and chloroform. The structure of charcoal is characterized by Fourier Transform Infra Red, X-Ray Diffraction and Scanning Electron Microscopy. Carbonization at ³ 405 oC for 5 hours produced well done charcoal, whereas carbonization at < 450 oC produces half done charcoal. Carbonization at 505oC produced best quality of charcoal, when compared to other treatment. The charcoal contained 2.426% water, 18.297% evapourable material, 12.22% ash, 69.48% carbon, and 6634 cal.. The adsorption capacity of the charcoal according to iodine solution and benzene gas were 379.80 mg/g and 12.37% respectively. The chloroform adsorption capacity was 11.69%, while the adsorption ability of charcoal resulted from carbonizing at 510 oC was 12.80%. The charcoal was composed of OH functional group, C-H, C-C, C-H aliphatic and C-O ether. Generally, the level and interval among charcoal crystalic layer that resulted from all carbonization treatment was not significant. Charcoal surface topography structure design showed more pore formation with the higher carbonization temperature.